1996
DOI: 10.1021/ma951073j
|View full text |Cite
|
Sign up to set email alerts
|

Free Volume and the Mechanism of Plasticization in Water-Swollen Poly(vinyl alcohol)

Abstract: Poly(vinyl alcohol), PVOH, films have been studied as a function of water content. The states of water present in the polymer (bound or free) have been characterized and are a function of water content. The effects of water content (and hence state) on the free volume, chain mobility, and glass transition (T g) behavior have been studied by positron annihilation lifetime spectroscopy, 13C solid state nuclear magnetic resonance, and dynamic mechanical analysis. The addition of approximately 30 wt % water result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
234
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(243 citation statements)
references
References 42 publications
8
234
0
1
Order By: Relevance
“…The enormous increase in 3 from 1.4 ns to 2.1 ns on uptake of 6 wt % water is similar to that observed when dry PVOH (T g ϭ 86°C) is plasticized with 28 wt % water (T g ϭ Ϫ28°C). 25 The other notable feature of these diagrams is the complete reversibility obtained after drying the "wet" sample at 40°C under vacuum. Clearly the absorption and desorption of water do not appear to change the PALS free volume characteristics of the sample.…”
Section: Resultsmentioning
confidence: 97%
“…The enormous increase in 3 from 1.4 ns to 2.1 ns on uptake of 6 wt % water is similar to that observed when dry PVOH (T g ϭ 86°C) is plasticized with 28 wt % water (T g ϭ Ϫ28°C). 25 The other notable feature of these diagrams is the complete reversibility obtained after drying the "wet" sample at 40°C under vacuum. Clearly the absorption and desorption of water do not appear to change the PALS free volume characteristics of the sample.…”
Section: Resultsmentioning
confidence: 97%
“…Experimental studies provide valuable understanding of the macroscopic [4][5][6][7][8][9] and microscopic [10,11] properties of polymers and their transport properties. Michaels and co-workers [4,5] found that there is a slight increase in the solubility of oxygen in polyethylene between 285 and 315 K, and that a further increase in temperature results in a far larger solubility.…”
Section: Introductionmentioning
confidence: 99%
“…I n p u r e P V A , t h e h y d r o g e n bonds are the dominant interaction responsible for both structure and molecular dynamics. As a consequence of these bonding interactions, water is capable to destroy inter-and intra-chain hydroxyl bonds, affecting PVA's crystalline regions and acting as a plasticizer, increasing the free-volume of the amorphous phase (Hodge et al 1996). On the other hand, in PVA/MMT nanocomposites, the interactions of the surface of the clay with the polymer can be attributed to the formation of hydrogen bonds between the PVA hydroxyl groups and the negatively charged clay surface (Grunlan et al, 2004), (Hernández et al, 2008).…”
Section: Pva/mmt Nanocompositesmentioning
confidence: 99%